THE ANALYSIS OF CSR PRACTICE IN PT. TELKOM (Case Study on CDC PT TELKOM MALANG) - Maria Dias Ika Salama; Noval Adib (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This descriptive qualitative study aims to analyze the CSR practices in PT TELKOM, whether it performs in accordance with the principles of CSR. Beside the practice of CSR in PT TELKOM Malang, the problem and solutions occurred in the implementation of CSR in PT TELKOM also are discussed. Case study is employed as the research design to answer the research questions. Furthermore, the data collection methods used in this study are interview, documentation and observation. The results in this study reveals that first, CSR practices in PT TELKOM are performed by supporting unit named Community Development Center (CDC). CDC has two main programs that are Partnership Program and Community Development Program. Through these two programs CSR practices in PT TELKOM has been implemented in accordance with the CSR regulations in Indonesia namely, Finance Minister of Indonesia Decision No. 1232/KMK.013 /1989 about Guidelines for Development Low-Income Entrepreneurs and Cooperatives through State-Owned Enterprises, Act No. 19 of 2003 about State-Owned Enterprises and Regulation of State-Owned Enterprises Minister Per-05/MBU/2007. Second, the problem occurred in the implementation of CSR in PT TELKOM is bad credit. The solution performed to overcome the existing problem should not be contrast with the CSR regulation in Indonesia and should prioritize the public interest around the company. There are four steps are applied as the solution such as reminding call, reminding letter, direct visit to the business location or domicile of the partners and credit payment rescheduling.Key words: Corporate Responsibility, Regulation, Indonesia, Implementation of CSR, PT Telekomunikasi Indonesia Tbk.